2002
DOI: 10.3917/nqf.213.0014
|View full text |Cite
|
Sign up to set email alerts
|

Identités plurielles des hommes mossi (Burkina Faso) : entre autonomie et précarité

Abstract: Distribution électronique Cairn.info pour Éditions Antipodes. © Éditions Antipodes. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Although the impact of young men's characteristics on their transition to marriage in Africa has attracted little attention compared to women's, a growing number of studies have recently shown the determining effect of economic activity on union formation among younger cohorts of city dwellers, and illustrated the marginalization of unemployed men on the marriage market (Antoine, 2006;Bocquier, Khasakhala, 2009;Calvès, 2007;Pike, 2016). The rising cost of bridewealth and of wedding expenditures, and the fact that these costs are increas-ingly borne by the groom alone in several African countries including Burkina Faso, are believed to explain this critical role played by male employment in the contemporary delayed transition to first union (Mokomane, 2005;Attané, 2002;Masquelier, 2005).…”
Section: Youth Employment Crisis Failed Masculinity and Gender Tensimentioning
confidence: 99%
See 1 more Smart Citation
“…Although the impact of young men's characteristics on their transition to marriage in Africa has attracted little attention compared to women's, a growing number of studies have recently shown the determining effect of economic activity on union formation among younger cohorts of city dwellers, and illustrated the marginalization of unemployed men on the marriage market (Antoine, 2006;Bocquier, Khasakhala, 2009;Calvès, 2007;Pike, 2016). The rising cost of bridewealth and of wedding expenditures, and the fact that these costs are increas-ingly borne by the groom alone in several African countries including Burkina Faso, are believed to explain this critical role played by male employment in the contemporary delayed transition to first union (Mokomane, 2005;Attané, 2002;Masquelier, 2005).…”
Section: Youth Employment Crisis Failed Masculinity and Gender Tensimentioning
confidence: 99%
“…With a growing number of young city-dwellers forced to live with their parents longer and to remain single because they feel they cannot afford to do otherwise, observers throughout Africa report high levels of bitterness and frustration among male youths who feel «stuck» in poverty and are unable to take the expected social steps toward adulthood of marriage and residential independence (Sommers, 2012;Mains, 2012;Attané, 2002;Mazzocchetti, 2010). In a context where becoming a household head who provides for his family remains a keystone of masculinity construction, failure to do is perceived as a form of «male disempowerment» (Silberschmidt, 2001) or of «failed masculinity» (Sommers, 2012).…”
Section: Youth Employment Crisis Failed Masculinity and Gender Tensimentioning
confidence: 99%
“…Not surprisingly, Meekers' study (1995) showed that partner selection was more likely to be controlled by parents when marriage took place at early ages. As for birth order, anthropological evidence from urban Burkina Faso (Attané, 2002) suggests substantial differences in the ability of young city dwellers to freely choose their partners, depending on their rank among siblings. Although arranged marriages used to be more common among the eldest sons, Attané's study suggests that today, contrarily, first-borns are granted more freedom in their choice of future spouses compared to their younger siblings.…”
mentioning
confidence: 99%